Analisa Perbandingan Tahanan Pembumian Peralatan Elektroda Pasak pada Gedung Laboratorium Teknik Universitas Borneo Tarakan - Achmad Budiman (JURNAL NASIONAL TEKNIK ELEKTRO, 2017)
Earthing systems are less well able to cause damage to electrical equipment. The risks are more current can not be optimally channeled back to earth. The smaller the resistance value, The better the earthing system. In certain soil conditions, grounding resistance value is also influenced by the depth of planting electrodes. The measurement results one ground rod resistance value with each length of 1.5 m and 2 m, diameter 0.045 m, respectively depth of 3 m and 3.25 m in Building Engineering Laboratory of the University of Borneo Tarakan successively obtained values of R (earthing) amounted to 12.76 Ω and 12 Ω while the calculation, the value of R (earthing) of 12.85 and 12.10 Ω Ω with the average value of muddy clay resistivity (ρ) of 38.58 Ω-m and 38.84 Ω-m. The installation of a ground rod 1,5m  of minimum 3 pieces in parallel has an R (earthing) value of 4.28 Ω complied with General Term Electrical Installation (PUIL 2000) ≤ 5 Ω and minimum installation distance between electrodes of 2 (two) times in length.Keywords : single rod electrodes, resistivity, earthing resistance.Abstrak - Sistem pembumian yang kurang baik dapat menyebabkan kerusakan pada peralatan listrik. Resiko yang ditimbulkan adalah arus lebih tidak dapat disalurkan secara maksimal kembali ke bumi. Semakin kecil nilai tahanan pembumian maka semakin baik sistem pembumiannya. Pada kondisi tanah tertentu, nilai tahanan pembumian juga dipengaruhi oleh kedalaman penanaman elektroda.  Hasil pengukuran nilai tahanan pembumian elektroda pasak tunggal dengan panjang masing-masing 1,5 m dan 2 m, diameter 0,045 m, masing-masing kedalaman 3 m dan 3,25 m pada Gedung Laboratorium Teknik Universitas Borneo Tarakan berturut-turut diperoleh nilai R(pembumian) sebesar 12,76 Ω dan 12 Ω sedangkan hasil perhitungan diperoleh nilai R(pembumian) sebesar 12,85 Ω dan 12,10 Ω dengan nilai rata-rata tahanan jenis tanah liat berlumpur (